2015
DOI: 10.1103/physrevd.92.052006
|View full text |Cite
|
Sign up to set email alerts
|

Search for the proton decay modepν¯K+with KamLAND

Abstract: We present a search for the proton decay mode p →νK þ based on an exposure of 8.97 kton-years in the KamLAND experiment. The liquid scintillator detector is sensitive to successive signals from p →νK þ with unique kinematics, which allow us to achieve a detection efficiency of 44%, higher than previous searches in water Cherenkov detectors. We find no evidence of proton decays for this mode. The expected background, which is dominated by atmospheric neutrinos, is 0.9 AE 0.2 events. The nonbackgroundsubtracted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…using our value of the gauge coupling constant g at the unification scale. At present, Super-Kamiokande has found that τ / Br(p → e + π 0 ) > 8.2 × 10 33 yr [23], and KamLAND has found that τ (p → νK + ) > 5.4 × 10 32 yr [24]. Thus the scenario of eq.…”
Section: A Gauge Unificationmentioning
confidence: 88%
“…using our value of the gauge coupling constant g at the unification scale. At present, Super-Kamiokande has found that τ / Br(p → e + π 0 ) > 8.2 × 10 33 yr [23], and KamLAND has found that τ (p → νK + ) > 5.4 × 10 32 yr [24]. Thus the scenario of eq.…”
Section: A Gauge Unificationmentioning
confidence: 88%
“…The product of these interactions, after integrating out S, generate O 3 at tree level. 5 Thus, unless there is a strong hierarchy between the different Yukawa interactions, one expects that the treelevel contribution dominates the decay rate. One can eliminate such an unwanted hierarchy in couplings using additional symmetries.…”
Section: A General Discussionmentioning
confidence: 99%
“…where the subscripts 1 and 3 in Eqs. (4) and (5) indicate the electroweak SUð2Þ representation of the bilinears of the fermions. The contraction of all the indices on the operators is explicitly shown in Appendix.…”
Section: Proton Decay Operators At One Loopmentioning
confidence: 99%
See 1 more Smart Citation
“…KamLAND is the first large scintillator detector to demonstrate the ability to search for these decays using PMT waveform data to identify the signal. Their search obtained a 44.4 ± 5.3% signal efficiency with a background rate of 101 ± 22 ev/Mton/yr [18]. No candidates were found in an 8.97 kton-yr exposure of the detector, resulting in a limit of τ p < 5.4 × 10 32 years (90% C.L.).…”
Section: Proton Decaymentioning
confidence: 98%